Tanggung Jawab Sosial Perusahaan (CSR) dan Keunggulan Bersaing - Nur Faliza (Universitas Malikussaleh, 2021)
This study is an empirical study that aims to analyze the effect of corporate social responsibility (CSR), human capital toward competitive advantage. The type of data used in this study is primary data from questioner (research instrument) that used self- administrated technique. The number of samples in this study were 100 managerial and non managerial employee with convenient sampling method. The analysis model used in this research is PLS-SEM using SmartPLS 3. The result show that the CSR and human capital have positive and significant effect on competitive advantage. The human capital as the mediation variable between relationship CSR and competitive advantage. Tthe Companies that develop and practice CSR will be able to increase human resources within the company to achieve a competitive advantage